Factores ambientales que controlan la producción de escorrentía y sedimento en el matorral semiárido del sector central de la depresión del Ebro (bajo valle del Gállego, Zaragoza). El papel de la pedregosidad, la vegetación y el suelo - Sebastián, María; Sesé, Pedro; Echeverría, María Teresa; Lasanta, Teodoro; Pérez-Cabello, Fernando; Ibarra, Paloma; De la Riva, Juan (Geographicalia, 2015)
An interpretation of the soil hydromorphological behaviour in the semi-arid central sector of the Ebro Depression is presented. 25 different simulations of rain in microenvironments with various environmental factors such as vegetation cover, stone density or previous soil moisture have been carried out on a hillside covered by scrubs and subjected to occasional grazing. From a statistical analysis of the results, the influence of the various environmental factors in the hydromorphological behaviour of the semi-arid scrub has been evaluated.
Keywords: Runoff; sediment production; rain simulation; semiarid area; central sector of the Ebro Basin.